Association between parental exposure to metal mixture and preterm birth: A prospective birth cohort study - Bo Yang; Yiyuan Chen; Haowen Zhang; Yuxin Liu; Cong Liu; Hong Lv; Tao Jiang; Rui Qin; Shiyao Tao; Xin Xu; Yuanyan Dou; Kang Ke; et al. (Ecotoxicology and Environmental Safety)
Accumulating evidence suggests that maternal prenatal exposure to metals is associated with preterm birth. However, the relationship between paternal metals exposure and preterm birth remains unclear. In current study, we assessed the association of paternal exposure, maternal exposure and parental co-exposure to metals with the risk of preterm birth, using data from the Jiangsu Birth Cohort (JBC) study. Urine samples collected from 1680 couples during the first trimester were measured for 25 metals concentrations. In the multivariable logistic regression models, paternal and maternal urinary antimony (Sb) concentrations were associated with 45 % (paternal: Odds Ratio (OR), 1.45; 95 % Confidence Interval (95 %CI), 1.01–2.09) and 43 % (maternal: OR, 1.43; 95 % CI, 1.01–2.03) higher risk of preterm birth per ln-unit increase, respectively. Also, maternal urinary cobalt (Co) concentrations (OR, 1.45; 95 % CI, 1.02–2.06) and copper (Cu) concentrations (OR, 2.16; 95 % CI, 1.15–4.03) were significantly associated with an increased risk of preterm birth. In addition, maternal exposure to Cu and paternal exposure to Sb demonstrated a significant dose-response relationship, with trend test P-values of 0.037 and 0.015, respectively. These findings suggested that higher concentrations of Cu and Sb are associated with an increased risk of preterm birth. The Bayesian Kernel Machine Regression (BKMR) models revealed a positive joint effect on preterm birth that intensified across increasing quantiles of parental mixture concentrations. Our findings emphasize that metals influence the onset of preterm birth through both maternal and paternal exposure. These results lay a theoretical foundation for developing risk assessment models based on parental exposure characteristics, offering deeper insights into the etiology of preterm birth. Furthermore, they provide essential scientific evidence to support its prevention and control strategies.